Molecular Diagnosis of Human Papillomavirus: Comparison Between Cervical and Vaginal Sampling - Ramzi R. Finan; Noha Irani-Hakime; Hala Tamim; Wassim Y. Almawi (Hindawi Limited, 2001)
Background: Human papillomavirus (HPV) is the most significant cause of cervical cancer. In view of the number of drawbacks associated with endocervical sampling, the gold standard for HPV detection, this study examined the utility and specificity of vaginal sampling as an alternative for endocervical sampling for the routine detection of HPV.